2022
DOI: 10.1186/s12911-022-01868-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating breast cancer websites targeting Arabic speakers: empirical investigation of popularity, availability, accessibility, readability, and quality

Abstract: Background Nowadays, patients have access to all types of health information on the internet, influencing their decision-making process. The Middle East and North Africa (MENA) region consists of 22 countries with an estimated population of around 600 million. Breast cancer is the highest diagnosed cancer in this region. Websites are commonly the go-to cancer information sources. A large population of the MENA region is only fluent in the Arabic language, thus access to Arabic websites is in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…It was found that the majority of websites failed to achieve an acceptable readability score, indicating that even individuals with a primary education may struggle to comprehend their content. We have con rmed the ndings of previous studies that analyzed the readability of Turkish government websites [27], [55], hospital web pages [52], [53], and university websites [31].…”
Section: Discussionsupporting
confidence: 80%
“…It was found that the majority of websites failed to achieve an acceptable readability score, indicating that even individuals with a primary education may struggle to comprehend their content. We have con rmed the ndings of previous studies that analyzed the readability of Turkish government websites [27], [55], hospital web pages [52], [53], and university websites [31].…”
Section: Discussionsupporting
confidence: 80%
“…Correspondingly, this tool is a beneficial scale that offers health information with high quality. It demonstrates the intent of a website to publish transparent information (Flint et al, 2021 ; Jasem et al, 2022 ; Smekal et al, 2019 ; St John et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, videos, images, figures and tables in the text, website URLs, punctuation marks, references, telephone, addresses, and author information were not included in the evaluation to avoid false results. [ 18 , 19 ] Of the first 200 websites obtained using the search term, 24 duplicate websites were removed, resulting in 176 websites. Further, after rigorous evaluation according to the exclusion criteria, 74 websites were removed and 102 websites were finally included in this study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is no official rule, it is believed that if the information cannot be accessed in 3 clicks, the user has not achieved the purpose and will leave the site. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%